(untitled) (Journal of Parents and Teachers, 2024)
The article describes how children perceive death, depending on their ages, experiences, and imagination. It continuously poses questions, and when individuals experience the loss of a loved one, they become aware of what has happened, as they go through different stages of grief until they learn to live with it.